2017
DOI: 10.1155/2017/3538568
|View full text |Cite
|
Sign up to set email alerts
|

A New Network-Based Strategy for Predicting the Potential miRNA-mRNA Interactions in Tumorigenesis

Abstract: MicroRNA (miRNA) plays an important role in the degradation and inhibition of mRNAs and is a kind of essential drug targets for cancer therapy. To facilitate the clinical cancer research, we proposed a network-based strategy to identify the cancer-related miRNAs and to predict their targeted genes based on the gene expression profiles. The strategy was validated by using the data sets of acute myeloid leukemia (AML), breast invasive carcinoma (BRCA), and kidney renal clear cell carcinoma (KIRC). The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Since a single miRNA has the potential to target multiple mRNAs, it is generally involved in regulating various biological processes and signaling cascades. 42 In addition, the aberrant expression of miRNAs is reported in many diseases. Therefore, it is essential to identify key miRNAs and their target genes in the development of miRNA-based therapeutics in MB.…”
Section: Discussionmentioning
confidence: 99%
“…Since a single miRNA has the potential to target multiple mRNAs, it is generally involved in regulating various biological processes and signaling cascades. 42 In addition, the aberrant expression of miRNAs is reported in many diseases. Therefore, it is essential to identify key miRNAs and their target genes in the development of miRNA-based therapeutics in MB.…”
Section: Discussionmentioning
confidence: 99%
“…Network construction refers to obtaining a large number of relevant data sets through data mining [28] or from various databases, websites, and experimental data and carrying out attribute mapping through network visualization tools, namely comprehensive data visualization [29]. Some types of constructed networks are protein-protein interaction (PPI) networks [30], gene interaction networks [31], and miRNA-mRNA interaction networks [32]. After the network is built, the processes of the two approaches diverge.…”
Section: Network-based Methodsmentioning
confidence: 99%
“…By constructing and analyzing the gene interaction network in Cytoscape, nine hub genes were obtained as potential therapeutic targets for new drug development [31]. Xue et al [32] constructed a miRNA-mRNA interaction network using miRNA and mRNA expression data, and the clinical data of three cancer types downloaded from The cancer genome atlas (TCGA) database [143]. The top 20 miRNAs with the highest degree in each data set were annotated via miR-Cancer (a microRNA-cancer association database) [144], miR2Disease (a microRNA-disease database) [145], and the Human microRNA Disease Database (HMDD) [146].…”
Section: Network-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs, which are 18-22 non-coding RNAs, regulate proteins expression by post-transcriptionally and extensive molecular mechanisms in various cancer types via either oncogenic or tumor-suppressive activities [ 5 ]. Substantive reports have indicated that the levles of miRNAs during the progression of colorectal cancer (CRC) altered, which highlighted their crucial roles for disease diagnostic and prognostic of CRC [ 6 ].…”
Section: Introductionmentioning
confidence: 99%